Pengaruh Model Pembelajaran Laps (Logan Avenue Problem Solving)-Heuristik Terhadap Kemampuan Pemecahan Masalah - Ira Silviana Rahman; Nerru Pranuta Murnaka; Wiwik Wiyanti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
The background of this research is the mathematics problem solving skill of students that had not been developed optimally. One of the learning models thatâ€™s expected to increase problem solving skills is LAPS (Logan Avenue Problem Solving)-Heuristic. The aim of this research is to compare the increase of mathematics problem solving skill between students who were taught by using LAPS-Heuristic model and conventional method. The kind of this research was quasi experimental by using nonequivalent control group design. Sample selection method used was cluster sampling that was obtained from grade VIII.3 as the experimental group learning using LAPS-Heuristic and VIII.2 as control group learning using conventional learning in SMPN 9 Tangerang. Instrument that was used in this research were test of mathematics problem solving and worksheet. The n-gain acquired from the experimental class amounted to 0.379 and 0.261 for the control class. Based on test results obtained by the hypothesis the t-value is greater than t'. The result of this research shows that the increase of mathematics problem solving skill of students who were taught by using LAPS-Heuristic model was higher than those taught with conventional method.Â